Industry 4.0 and University Performace Based on Prism Theory - Tri Siwi Nugrahani; Yuni Nustini; Imanda Firmantyas Putri; Teguh Erawati; Evi Grediani (Journal of Business and Management Review, 2021)
This article aims to evaluate the performance of higher education based on the Higher Education National Standard (SN) which is implemented with the performance of Prisma. Prisma performance appraisal is able to assess the performance of all entities from various stakeholders including for universities in Indonesia. Every Prism performance appraisal goes through a satisfaction orientation, strategy, process, capability and contribution. Prism is very suitable for organizational assessment, especially in the era of the Industrial Revolution 4.0 because every aspect will always be related and affect performance achievement. Prism-based higher education performance studies by compiling Higher Education Standards can be used to add references as a measure of the level of satisfaction of stakeholders and can improve PT performance internally